Kepemimpinan Autentik dan Kualitas Pelaporan Keuangan: Peran Iklim Etis - Sasongko, Sonnya Nurman; Kuang, Tan Ming (Politeknik Ganesha Medan, 2024)
Financial reports are a crucial factor that can influence economic decision-making. Accountants are responsible for producing high-quality financial reports that provide transparent, accountable, and reliable information. Although there have been numerous studies examining the factors that can affect the quality of financial reporting, research investigating the impact of leadership style and ethics on financial reporting quality is still limited. Therefore, this study aims to examine the influence of authentic leadership on the quality of financial reporting, moderated by the ethical climate. A survey questionnaire was used to collect primary data in a quantitative approach. The Authentic Leadership Questionnaire (ALQ) was employed to measure authentic leadership, while the ethical climate was measured using a questionnaire based on the research by Qualls & Puto (1989). The quality of financial reporting was measured using a questionnaire developed by Iqbal & Javed (2017). The sample for this study consists of management accountants, financial accountants, public accountants, and accountants in the public sector. Finally, the hypothesis testing in this study employed the Structural Equation Modelling-Partial Least Squares (SEM-PLS) analysis method. This research reveals a positive influence of authentic leadership and ethical climate on the formation of high-quality financial reports. The ethical climate strengthens the relationship between authentic leadership and financial reporting quality. To improve financial reporting quality, this study suggests the importance of authentic leadership in the selection, promotion, and development of leaders, as well as the creation of an ethical culture in organizations.